Farm-to-fork investigation of an outbreak of Shiga toxin-producing Escherichia coli O157. Issue 3 (28th February 2018) - Wilson, Deborah; Dolan, Gayle; Aird, Heather; Sorrell, Shirley; Dallman, Timothy J.; Jenkins, Claire; Robertson, Lucy; Gorton, Russell
Abstract : Fifteen cases of Shiga toxin-producing Escherichia coli (STEC) O157 infection were associated with the consumption of contaminated food from two related butchers' premises in the north-east of England. Ten cases were admitted to hospital and seven cases developed haemolytic uraemic syndrome. A case control study found a statistically significant association with the purchase of raw and/or ready-to-eat (RTE) food supplied by the implicated butchers' shops. Isolates of STEC O157 were detected in two raw lamb burgers taken from one of the butchers' premises. Subsequent environmental sampling identified STEC O157 in bovine faecal samples on the farm supplying cattle to the implicated butchers for slaughter. Whole genome sequencing (WGS) was performed on the Illumina HiSeq 2500 platform on all cultures isolated from humans, food and cattle during the investigation. Quality trimmed Illumina reads were mapped to the STEC O157 reference genome Sakai usingbwa-mem, and single nucleotide polymorphisms (SNPs) were identified usinggatk2 . Analysis of the core genome SNP positions (>90 % consensus, minimum depth 10×, mapping quality (MQ)≥30) revealed that all isolates from humans, food and cattle differed by two SNPs. WGS analysis provided forensic-level microbiological evidence to support the epidemiological links between the farm, the butchers' premises and the clinical cases. Cross-contamination from raw meat to RTE foods at the butchers' premises was the most plausible transmission route. The evidence presented here highlights the importance of taking measures to mitigate the risks of cross-contamination in this setting.